(untitled) (Research, Society and Development, 2025)
Gastric cancer is the second leading cause of death from neoplastic diseases globally. In Brazil, both the incidence and mortality rates are high in both sexes, and the high severity of the disease is related to late diagnosis. In Brazil, approximately 625 thousand new cases were registered each year between 2020 and 2022. The main associated risk factors include alcohol consumption, family history of cancer, overweight, smoking, and Helicobacter pylori infection. This study aims to analyze deaths from malignant gastric neoplasia in adults aged 20 to 59 in Brazil between 2022 and 2023. The research was retrospective and descriptive, using data from DATASUS during the month of October 2024. An Excel database was created and indicators such as sex, region, age group, and race were analyzed. From 2022 to 2023, Paraná recorded 439 deaths from malignant gastric neoplasm in adults aged 20 to 59, with a higher incidence in men (63.78%). The most affected age group was 50 to 59 years (62.89%), with a predominance of deaths among white individuals 303 (64.60%). These data highlight the need for preventive strategies and more equitable health policies to reduce inequalities in access to medical care and improve the well-being of the population of Paraná.